Les horizons de Thomas Hardy - Marianne Camus (Cahiers Victoriens et Edouardiens)
Thomas Hardy’s fiction is generally regarded as concerned with the hopelessness of the human condition in an indifferent universe. But Hardy’s heroes are also clearly situated in the society of their time. This article will look at two of the socially determined patterns that contribute to the failure which they usually encounter in their quest for a horizon beyond the class and place where they were born : the inability to construct a horizon and the adoption of a horizon in simple reaction to the environment. The inability to construct a horizon will be analysed through Tess, whose future is destroyed by her status as a fallen woman and the characters of The Woodlanders, lured by their hopes of social betterment. The notion of a reactive horizon will be analysed through the protagonists of The Return of the Native and Jude the Obscure. The heroes of Far from the Madding Crowd and Two on a Tower will be used to confirm the point a contrario.